From Digitalization to Humanization: Building Collaborative and Impactful Higher Education Models through Technology Integration - Pieter Sahertian; Maris Kurniawati (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
This paper aims to examine the shift from digitalization to humanization in higher education by proposing an integrated model that balances technological innovation with human-centered values. It seeks to demonstrate how digital transformation can enhance rather than diminish empathy, social connectedness, and ethical learning in universities. Using a qualitative–descriptive approach supported by case analyses from several higher education institutions, the study reviews practices, policies, and learning innovations to identify patterns that integrate technology with humanistic educational principles. The analysis reveals three essential pillars for designing impactful higher education models: (1) collaborative digital ecosystems that foster interdisciplinary engagement and knowledge co-creation; (2) humanized learning experiences that emphasize emotional intelligence, inclusion, and social interaction; and (3) adaptive institutional strategies that align digital integration with organizational culture and broader societal needs. The findings show that ethically designed and inclusive digital tools can strengthen critical thinking, empathy, and community-oriented innovation among learners and educators. The study concludes that technology in higher education should function as an enabler of human potential rather than a substitute for human interaction. A human-centered digital transformation ensures sustainable, meaningful, and future-ready learning environments, offering practical implications for policymakers, educators, and institutional leaders committed to designing more humanized digital ecosystems.